Assessing the cluster potential of the Eastern Visayas Food Processing Industry - Radam, Marilyn O.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, Technology Management Center, 2012)
The food processing industry, as a major component of agri-business, is consistently identified as a key sector for investment priority in the Eastern Visayas Regional Development Plan. Considering the region's diverse agricultural and fishery resources, processing these natural resources into higher value products will bring greater economic benefits. However, the dismal regional macroeconomic performance implies the need for enhancements in the development initiatives being pursued. The clustering of industries in national and sub-national levels as an economic development model has been proven successful in many advanced and developing countries worldwide. A cluster-based development approach is a strategic framework to enhance growth of the regional economy or industry since it encourages diagnosis of economic challenges and opportunities to determine sources of competitiveness; and identifies areas that are likely to have the greatest long-term impact. This study assesses the cluster potential of the Eastern Visayas food processing industry which consequently necessitates an analysis of the industry's status, trends, prospects, opportunities and challenges for growth. Since cluster initiatives are primarily geared toward increasing competitiveness, the science and technology interventions required for the development of the industry cluster are also identified. In particular, key roles for the DOST are herein proposed being the government agency mandated to pursue a S&T agenda and innovation policies to address critical technological issues and needs of the industry. Policy agenda and directions are usually broadly articulated and designed for implementation across different sectors or regions. The diverse conditions and varied dynamics of the interrelationships among industry players in different sectors and regions may require different development approaches and strategies. An industry assessment and review of the development initiatives is therefore requisite for industry cluster development. A qualitative research design is adopted in the assessment of the industry using both secondary and primary data as sources of information. The secondary data from reports, previous studies and publications were accessed through internet search and personal visits to relevant source institutions. The primary data were obtained through semi-structured survey-interview of firm-respondents and non-firm key informants selected in a deliberate and non-random fashion following a purposive sampling design. The primary and secondary data collection was undertaken in December 2011 to March 2012 in all the six provinces of the region with survey-interview conducted in the last two months. The short time span to conduct the study is the major limiting factor in the number of respondents considered in the study. A total of 28 firm-respondents and 14 non-firm key informants were the primary sources of information and provide some of the details required for in-depth analysis and in the validation of secondary data. The Diamond Model of Porter (1990) in determining national competitive advantage or of a particular industry sector provides the theoretical framework in analyzing the industry which considers four interrelated determinants of competitiveness, the role of government and chance events. Other analytical tools such as industry cluster mapping, industrial value chain diagnosis and SWOT analysis are also utilized to exhaustively extract all thematic and relevant information from the qualitative materials gathered. The study finds that "clustering" is not yet a formally organized initiatives in the food processing industry of Eastern Visayas since a unified and targeted regional development program specific for the sector is still non-existent whereby collaborative activities among key industry players are focused and deliberately planned. Although, the different government agencies and LGUs are implementing enterprise development programs, these are broadly directed for the entire industrial sector spanning several sub-sectors. However, some factors and conditions existing in the industry point to a potential cluster that could develop if appropriate actions are taken. First, the presence of a critical mass of MSMEs with complementary assets which can be linked together to achieve economies of scale and create collective efficiency. These MSMEs possess traditional knowledge and skills that enable them to produce unique products utilizing diverse agricultural and fishery resources of the region that have potentials for domestic and export markets. Second, the existing networking among MSMEs is a positive indication for collaboration which is essential in cluster development. Third, government support is evident in the form of the different programs and assistance package available for the MSMEs. The frameworks for networking among government agencies, LGUs, financing institutions and MSMEs are also present. Fourth, the presence of higher education institutions with research facilities to undertake R&D activities could provide the innovation and technology development support including technical manpower that are critical for industry cluster development.
The industry is also contrained by several interrelated factors. Foremost are the low production capacities and technological levels of the firms resulting to uncompetitive manufacturing operations - e.g. low productivity, low production level, poor packaging/labeling, inflexibility to adapt to changing market trends and non-compliance to regulatory standards. The uncompetitive product quality and low production volume do not encourage aggressive marketing. The low investment by MSMEs in technology upgrading is accounted for inaccessibility to capital inputs. The failure of some enterprises to successfully realize benefits from technology upgrading through the DOST SETUP may point to low management and entrepreneurial skills because of their inability to seize opportunities and make business venture works. Using Porter's diamond model, it is evident that the food processing industry in the region possesses both positive and negative elements under the different determinants of competitiveness - e.g. firm strategy/structure and rivalry, factor conditions, demand conditions, and related and support industries. The government assumes a critical role in initiating the development of the industry and in providing the environment that creates appropriate balance among the four determinants to harness the competitiveness of the industry. Considering the deficiencies of the industry, S&T interventions are most critical in : (1) upgrading manufacturing operations for a more competitive production system through application of new technologies to improve traditional knowledge, enhance production efficiency, and increase competitiveness of products ; (2) product innovations and diversification to maximize value addition to diverse agricultural and fishery resources; (3) R&D to standardize indigenous processing technologies to establish quality standards for ethnic products of the region; (4) design of appropriate packaging for ethnic products that retain uniqueness, improve marketability, withstand inefficiencies in transport system, and comply with standards and regulations in domestic and export markets. Aside from ensuring the provision of identified S&T interventions, the DOST Regional Office should assume key roles in the development of the industry cluster which include : (1) initiate the networking among technology developers and technical service providers in the region to build cooperation and linkages that will enhance coordination in policy and development initiatives; and ensure availability of technical services to the industry; (2) lead in the formulation of a Regional S&T agenda for the industry that spells out the R&D prioritization, strategies for technology and innovation development, and initiatives to build innovation capacities of enterprises; and (3) monitor and evaluate technological and innovative capacity of the cluster to determine its competitive performance to preempt its decline and ensure sustainability.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Food industry and trade; Technological innovation